Localization and Interaction between Kinin B1 Receptor and NADPH Oxidase in the Vascular System of Diabetic Rats - Haddad, Youssef; Couture, Réjean (Frontiers in Physiology, 2017)
Kinin B1 receptor (B1R) enhanced superoxide anion (O2●―) production in the vasculature of diabetic rats. This study investigates the induction and distribution of B1R in diabetic blood vessels and addresses the hypothesis that B1R is co-localised with NADPH oxidase (NOX1 and NOX2) and produces its activation via protein kinase C (PKC). Diabetes was induced in rats with streptozotocin (STZ 65 mg.kg‒1, i.p.). Two weeks later, the production of O2●― was measured in aorta rings in response to the B1R agonist (Sar[D-Phe8]-des-Arg9-BK, 20 μM) by the method of lucigenin-enhanced chemiluminescence. Various inhibitors were added (10 μM) to block PKCtotal (Ro-31-8220), PKCβ1/2 (LY333531) or NADPH oxidase (Diphenyleneiodonium).The cellular localization of B1R was studied in the aorta, popliteal artery and renal glomerulus/arteries by immunofluorescence and confocal microscopy with markers of endothelial cells (anti-RECA-1), macrophages (anti-CD11), vascular smooth muscle cells (anti-SMA) and NADPH oxidase (anti-NOX1 and NOX2). Although B1R was largely distributed in resistant vessels, it was sparsely expressed in the aorta’s endothelium. The greater basal production of O2●―in STZ-diabetic aorta was significantly enhanced by the B1R agonist (15-45 min). The peak response to the agonist (30 min) was inhibited by all inhibitors. Immunofluorescent staining for B1R, NOX1 and NOX2 was significantly increased in endothelial cells, vascular smooth muscle cells and macrophages of STZ-diabetic aorta on which they were found colocalised. Data showed that B1R enhanced O2●― by activating vascular NADPH oxidase through PKCβ1/2. This was substantiated by the cellular co-localisation of B1R with NOX1 and NOX2 and opens the possibility that B1R-enhanced oxidative stress derived from vascular and infiltrating immune cells in diabetes.